PENEGAKAN HUKUM KORUPSI POLITIK DI INDONESIA PERMASALAHAN DAN ISU-ISU KONTEMPORER (Jurnal Hukum Mimbar Justitia, 2019)
As we know that corruption is happening in Indonesia today, it has been in a very severe and entrenched position in every life. The development of corruption from year to year is increasing rapidly, both in losses suffered by the state and the quantity and quality that are increasingly systematic. The increase in corruption that is out of control will bring disaster to the life of the national economy and the life of the nation and state. The occurrence of corruption cases in Indonesia has no idea who the limits are, why or how. Even many state officials are corrupt. Not only only state officials who commit corruption. Now the corruption case in Indonesia seems to have been an ordinary thing and can be called a phenomenon. The implementation of a clean country is important and necessary to avoid corrupt practices in circulation which not only involve the state officials, but also their families and cronies, which if allowed by the Indonesian people will be in a disadvantaged position. Besides that, in practice there are still neglected matters, because the judges' decisions are unclear and unequivocal distinguish a nominal loss of the state lost due to the convict's actions. This means that the Judge has not distinguished a definition regarding the element of enriching or benefiting himself or anyone else. This difference should be put forward by the Judge in its decision, so that the classification between corruption acts that are detrimental to the state's economy (state losses have already occurred in real terms or state finances have also begun to decrease) should be seen. According to Nyoman Serikat Putra Jaya said that corruption is not only carried out by state administrators, or between state administrators, but also other parties, namely families, businessmen and cronies, so that damaging the welfare of the nation and state also endangers the existence of the country.Keywords: corruption, nepotism, state economy, welfare, collusion.